The Jumbies - Baptiste, Tracey (Chapel Hill, North Carolina : Algonquin Young Readers, 2015)
Eleven-year-old Corinne must call on her courage and an ancient magic to stop an evil spirit and save her island home.
Accelerated Reader AR